Effect of health insurance on outpatient health service utilization among households affected by non-communicable diseases in busia county, Kenya - Kemei, Wilson; Nyaberi, Jackline M.; Ruttoh, Simon K. (International Journal Of Community Medicine And Public Health, 2024)
Background: Non-communicable diseases (NCDs) are increasingly becoming important agents of illness and premature deaths globally, killing up to 41 million people annually, 77% of which occur in LMICs. In Kenya, major NCDs are cancer, diabetes, cardio-vascular and chronic respiratory diseases. They account for 50% of all hospital admissions and 39% of hospital deaths. Patients with NCDs go through expensive treatment regiments, restraining them from utilizing available care. NCDs deepen inequality and are the major drivers of unending poverty. Kenya successively reformed the National Health Insurer to include a package that cover the blight of NCDs and transform it into a primary enabler for achieving Universal Health Coverage. There is however no evidence whether health insurance (HI) improves utilization of outpatient NCDs care. This study examined whether health insurance has an effect on utilization of outpatient NCDs care among households of people with NCDs. Methods: A quasi-experimental design was conducted among eligible households with HI cover and those without, involving a representative sample of 350 households. Interviewers conducted interviews at baseline and after 1 year among household heads. Results: Utilization of outpatient NCDs care improved by 1.24 (95% CI=1.048-1.474) times among insured households, (p=0.012). Conclusions: Health insurance improves utilization of outpatient NCDs care. To accelerate progress towards UHC, national government should scale up the program to all counties. County government and partners should ensure availability of essential NCDs commodities.